Marketing Distribution Analysis of Tilapia (Oreochromis Niloticus): A Case Study of a Production House in Liabuku Village, Bungi District, Baubau City - Bone, Abdul Hadi; Failu, Ismail; Hamar, Bahtiar; Darmatia, Siti Fara; Repi, Jayanti Olviana; Yosianti M, Faharani (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
The area of Baubau City has an ocean area of 200 miles, has fishery potential that can support people's lives. This study aims to: (1) determine the marketing agency in the marketing distribution of tilapia; (2) Knowing what the marketing margin of tilapia is; (3) Analyzing strategies and policies for developing tilapia aquaculture. This research was carried out in a fish production house starting in July-September 2021. The research method used qualitative descriptive methods and literature searches. To analyze the marketing functions based on each marketing agency, while the distribution margin analysis is carried out by calculating marketing costs both at the consumer and producer level. The results showed that there were 3 marketing distribution patterns, namely: Pattern I (Producer-Consumer), Pattern II (Producer-Retailer-Consumer), Pattern III (Producer-Wholesale-Retailer-Consumer). The distribution level of tilapia marketing in channel pattern I is more dominantly used because the marketing distribution channel is relatively shorter and affordable so that it cuts the marketing distribution channel to the final consumer level, so as to reduce other additional costs.